Leishmanioses na faixa de fronteira: Perfil epidemiológico, difusão, agregação e priorização de áreas no Brasil - Ludmila Campos Lopes (2019)
Leishmaniasis accounts for two million new cases annually with endemic transmission in 98 countries. In the Americas, Brazil has the highest number of cases of the disease. In addition to the recognized relevance of the study of leishmaniasis in this country, data from the Brazilian border strip have generated interest as a public health problem. This reinforces the relevance of the study of leishmaniasis in this country, especially in the Brazilian border area. Thus, the main objective of this study was to analyze the epidemiological profile and spatial diffusion/clustering processes of tegumentary and visceral leishmaniasis in the border region of Brazil from 2009 to 2017. We performed an ecological study with the confirmed cases of LTA and LV notified to the Ministry of Health (Brazil). The epidemiological profile was described considering the following variables: gender, skin color/ethnicity, age range and years of schooling. Spatial analyzes were carried out dividing the study period in triennium: 2009 to 2011, 2012 to 2014 and 2015 to 2017. In order to verify the presence of spatial autocorrelation and determine the priority areas for surveillance and control of the disease, the global and local(LISA) Moran indices were calculated. Maps were developed with Terraview and Geoda softwares. In the period, the confirmed cases of LTA in Brazil were 176,132 of which 29,920 (17%) occurred in the border strip, with the respective detection coefficients: 9.76 / 100,000 inhabitants and 29.83 / 100.000. For LV, 33,684 cases occurred in Brazil, of which 6.28 (1.8%) belonged to the border with the incidence coefficients of 1.85 / 100.000 inhabitants and 0.61 / 100.000 inhabitants respectively. For the two clinical forms of leishmaniasis the largest number of cases were observed in males, skin color brown and low years of schooling similar to the data observed for Brazil. The prevalent age group for patients with the tegumentary form was 20 to 39 years old (42.21%) while in the visceral we observed younger than 10 years (48.09%). In indigenous, we found a high proportion of cases in the border strip for tegumentary form (6.66%) and visceral (17.52%) when compared with data for the whole country (3.22% and 1.05%, respectively). The analysis of the cases and incidence showed that the municipalities most affected were distributed in the North and Central regions (mainly in Amazon Region). Some municipalities with higher incidence of LTA were Serra do Navio (AP), Pedra Branca do Amapari (AP), Xapuri (AC) and Sena Madureira (AC) and for LV were Uiramutã (RR), Pacaraima (RR) and Normandia (RR). The Global Moran indices indicated positive spatial autocorrelation. The areas defined as highest priority for control in the three evaluated periods were 69 for LTA and for LV we found 4 areas distributed in the North and Central arcs of the border strip. This work may guide the development of more targeted and effective strategies that may contribute to the surveillance and control of leishmaniasis in the areas of Brazilian border strip. We also emphasize the importance of integration between border countries for better control of the disease.